The European Parliament and delegated legislation : an institutional balance perspective - Chamon, Merijn (London [England] : Hart Publishing, 2022)
"This book looks into the Treaty-law framework governing the delegation of legislative power in the EU as redefined by the Lisbon Treaty. It asks how this empowered Parliament operates, both in in relation to decision-making at the legislative level, looking at specific case studies, and the sub-legislative level, examining its scrutiny powers. By doing so, it illustrates if the Parliament's formally reinforced role is reflected in the actual balance of powers in the area of delegated legislation. This rigorous study gives a fascinating insight into one of the most significant developments in European parliamentary law-making, which EU constitutional lawyers will find required reading."--
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: European Parliament; European Economic Community; European Union countries -- Politics and government -- 21st century; Electronic books